Desain Arsitektur Data Administrator Kependudukan Sistem Informasi Desa - Firman Yudianto; Teguh Herlambang; Mukhtar Adinugroho; Nur Shabrina Meutia (UKInstitute, 2023)
Based on the 2014 Village Law on village autonomy and its tools, it is expected that each village must have an innovation and regulation of population system management in their respective villages. The village apparatus is a village located in the Jombang regency area that has an aggressive population in carrying out village development in the field of infrastructure along with an information system in population services and budgeting in development, so it needs innovation about the Village Information System that can provide convenience for the community in managing the population system and transparency in budgeting village costs. The use of village information systems will begin with the design of the population administrator's data architecture. This research uses the method used is the life cycle of waterfall system development and designing web-based and online population village information systems. This population administrator data architecture design will be able to provide convenience in managing the population system in the community to develop villages towards smart cities.